Follow-up of a Rickettsia felis encephalitis: Some new insights into clinical and imaging features. (March 2021) - Zeng, Ziling; Wang, Chunjuan; Liu, Cuicui; Wang, Baojie; Meng, Xin; Chen, Yan; Guo, Shougang
Highlights: A misdiagnosed case of Rickettsia felis encephalitis was confirmed by cerebrospinal fluid mNGS. Neuroimaging showed a focal lesion in the right thalamus which was indistinguishable from a glioma. Perivascular inflammation in the lesion implied a vasophilic characteristic of the pathogen. Rickettsia felis encephalitis could clinically display as none-specific neurological symptoms. Abstract: Rickettsia felis ( R. felis ) infection is a cause of unspecified encephalitis. However, the incidence has been underestimated due to the intracellular features of the pathogen and insufficient understanding of its clinical picture. This study reported a case of R. felis infection in a 26-year-old female who only manifested with certain neurological symptoms. With a lack of specific systemic inflammatory symptoms, the diagnosis was initially misdiagnosed as a brain glioma. However, a brain tissue biopsy showed prominent perivascular inflammatory infiltrations, which indicated inflammatory disease. Spinal fluid metagenomic next-generation sequencing (mNGS) was taken after ruling out other common infectious and autoimmune diseases. The results suggested R. felis infection, which was also supported by Weil-Felix reaction in the serum. After the diagnosis was corrected as R. felis encephalitis, the patient was successfully treated with doxycycline and had a good prognosis at the 1-year follow-up.